Menelusuri wacana pembangunan: Mencari format pembangunan khas negara berkembang - Arif Hartono (Economic Journal of Emerging Markets, 1999)
Development concepts in almost of developing countries have been being apdoted from western. Whereas, developing countries have been different background and condition from western in politics, economics, social, culture, history, etc. The implication of that condition, Western concepts shouldn't solve the real problem of development in developing countries. A situation was aggravated by the existence of world relationship that give more advantage to Western/developt countries.